Cycle tourist characteristics. - Zopiatis, Anastasios; Andreev, Hristo (My University, 2022)
The Encyclopedia of Tourism Management and Marketing is, quite simply, the definitive reference work in the field. Carefully curated by leading tourism scholar Dimitrios Buhalis, this is the largest tourism management and marketing ontology that has ever been put together and offers a holistic examination of this interdisciplinary field. Use the Search within Book (below right) or browse the list of entries alphabetically to navigate over 1200 entries from leading international scholars. An invaluable resource for academics, students and practitioners providing an ideal starting point for any research journey. The concise entries present an accessible and condensed overview of each topic and the selected references that follow each entry suggest directions for further detailed exploration.
Encyclopedia of Tourism Management and Marketing.
Keywords: Tourism Management; Travel; Tourist; Tourism Marketing; Tourism Encyclopedia